Optimalisasi Pemahaman Konsep IPA melalui Model Pembelajaran Project Based Learning di Madrasah Ibtidaiyah - Rahmansyah, Syahrul (Lembaga Anotero Scientific Pekanbaru, 2025)
This study was motivated by the low understanding of the concept of science material for class IV MI Al-Ikhwan Pekanbaru. This study aims to: (1) Know the application of the Project Based Learning model in increasing understanding of student science concepts, (2) increasing understanding of student science concepts through the Project Based Learning model. This type of research is Classroom Action Research (CAR). The research subjects used were all 30 students of IVA, totaling 30 students. Research consists of two cycles, each cycle consists of planning, implementation, action, observation, and reflection. Data collection techniques in the form of observations, tests, and interviews. Based on the results of the study there are 3 stages in the study that produced 3 results, namely the pre -cycle stage (9.5%), the 1 (100%) cycle stage, cycle 2 (100%) the percentage of students that exceeded the KKM score (> 75). Judging from the average value, it can be seen the difference between the three stages of the research is the stage Prasiklus (74.5) cycle 1 (79) and cycle 2 (96). From the results of this study it was concluded that the application of Project Based Learning learning models can increase understanding of concepts in student science subjects.